Emergence and Molecular Characterization of an Avian Hepatitis E Virus From Donglan Black Chicken in Southern China - Fu, Fumei; Deng, Qiaomu; Li, Qiuhong; Zhu, Weiyu; Guo, Jinhan; Wei, Ping (Frontiers in Veterinary Science, 2022)
Avian hepatitis E virus (HEV) is a major pathogen associated with hepatitis splenomegaly syndrome in chickens and has been reported in China. Phylogenetic trees, Bayesian analysis, positive selection sites screening and recombination analysis were firstly used to comprehend the global avian HEVs. All the avian HEV strains, including a new isolate named GX20A1 got from Donglan Black chicken in Guangxi, China, were uniformly defined into 4 genotypes, and GX20A1 belongs to Genotype 3. The topology of the phylogenetic tree based on the sequences of a 339-bp fragment (coding the helicase) in ORF1 of the avian HEVs was consistent with that based on the full-genome sequence. The estimated evolution rate of avian HEVs is 2.73×10-3 substitution/site/year (95% confidence interval (CI): 8.01×10-4-4.91×10-3), and the estimated genetic diversity of the strains experienced a declining phase from 2010 to 2017 and stabilized after 2017. It was further found that the Genotype 3 HEVs, including isolates from Hungary and China, likely originated in the 1930s. Notably, GX20A1 was gathered in the same branch with a Genotype 3 Guangdong isolate CaHEV-GDSZ01, which appeared earlier than GX20A1. In addition, two positive selection sites were identified, one for each of ORF1 and ORF2. Overall, the study revealed that avian HEVs were uniformly defined into 4 genotypes, and a 339-bp fragment in ORF1 of the viral genome could be used for the classification. A Genotype 3 isolate GX20A1 was first found from Donglan Black chicken and most likely originated from Guangdong.